Pengaruh Inflasi, Kebijakan Moneter, dan Volatilitas Pasar terhadap Perubahan Suku Bunga Pada Bank Pemerintah (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to examine the influence of inflation, monetary policy, and market volatility on interest rate changes in state-owned banks in Indonesia during the 2019–2024 period. A quantitative associative approach was applied using secondary data collected from official financial reports. The analysis involved multiple linear regression, t-tests, and F-tests. The t-test results revealed that only inflation had a significant and negative impact on interest rates, while monetary policy and market volatility did not show significant effects. Simultaneously, the F-test indicated that the three variables did not significantly influence interest rates, supported by a low Adjusted R² value of only 13.4%. These findings suggest that other external factors outside the model play a more dominant role in determining interest rate fluctuations. The results emphasize the critical importance of inflation control and the need for a more comprehensive approach in shaping interest rate policy within state-owned banking institutions.